2018
DOI: 10.1111/jcpt.12673
|View full text |Cite
|
Sign up to set email alerts
|

Calcium channel blockers and the incidence of breast and prostate cancer: A meta-analysis

Abstract: Although a statistically significant association between CCB use and incidence of BCa does exist, the limitations of the individual studies restrict the clinical application of this relationship. Our meta-regression model does newly identify a 9-year latency period of CCB use and a significantly increased risk of BCa. No significant association exists between CCB use and the incidence of PCa. Our meta-regression shows CCB may have a protective effect upon PCa incidence among older populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…However, they included studies up to 2012 and did not perform a duration effect analysis. 6,13 One proposed mechanism in which CCBs may induce cancer is the inhibition of apoptosis. 14 CCBs are prescribed for various cardiovascular conditions, including hypertension, angina pectoris, and arrhythmias.…”
Section: Introductionmentioning
confidence: 99%
“…However, they included studies up to 2012 and did not perform a duration effect analysis. 6,13 One proposed mechanism in which CCBs may induce cancer is the inhibition of apoptosis. 14 CCBs are prescribed for various cardiovascular conditions, including hypertension, angina pectoris, and arrhythmias.…”
Section: Introductionmentioning
confidence: 99%
“…In a Spanish population study, CCB consumption increased the odds of breast cancer in postmenopausal women; women with body mass index >25 kg/m 2 (OR, 2.54; 95%CI, 1.24‐5.22); and women with stage III‐IV cancer (OR, 2.70; 95%CI, 1.23‐5.95), nonductal cancer (OR, 2.63; 95%CI, 1.27‐5.43), and ErbB2+ cancer (OR, 2.52; 95%CI, 1.18‐5.37) . A meta‐analysis of 11 relevant studies with high heterogeneity by Thakur et al reported that the OR for the association between breast cancer and CCB use was 1.14 (95%CI, 1.02‐1.27; I 2 , 86.6%), and a 9‐year latency period of CCB use significantly increased the risk of breast cancer. Because tumor formation is a complex consequence of genetic mutations resulting from environmental and lifestyle factors, CCBs may not represent a major contributor to the development of breast tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is a lack of robust evidence on the association between CCB use and the majority of cancers, 41 a recent metaanalysis showed that an odds ratio (OR) of 1.14 for the association of breast cancer with CCB use (in particular a 9-year latency period of CCB use), while CCBs may have protective effect on prostate cancer among older populations. 42 A few studies showed that CCBs were associated with a better survival for various cancers, including GC. 23,43,44 However, to our knowledge, this is the first report on the potential chemopreventive effect of CCBs on GC using a well-defined cohort of H pylorieradicated subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of CCBs on cancer development also appear to vary in different organs. Although there is a lack of robust evidence on the association between CCB use and the majority of cancers, 41 a recent meta‐analysis showed that an odds ratio (OR) of 1.14 for the association of breast cancer with CCB use (in particular a 9‐year latency period of CCB use), while CCBs may have protective effect on prostate cancer among older populations 42 …”
Section: Discussionmentioning
confidence: 99%